2010
DOI: 10.1063/1.3329367
|View full text |Cite
|
Sign up to set email alerts
|

Cluster synchronization in networks of coupled nonidentical dynamical systems

Abstract: In this paper, we study cluster synchronization in networks of coupled non-identical dynamical systems.The vertices in the same cluster have the same dynamics of uncoupled node system but the uncoupled node systems in different clusters are different. We present conditions guaranteeing cluster synchronization and investigate the relation between cluster synchronization and the unweighted graph topology. We indicate that two condition play key roles for cluster synchronization: the common inter-cluster coupling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
132
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 57 publications
1
132
0
2
Order By: Relevance
“…where m * r = |π * r | is the size of the mEEP with respect to node r. Equation (37) states that the rank of the observability of a node under consensus dynamics is equal to the rank of the observability of its cell in the consensus dynamics of the corresponding quotient graph, and the size of the mEEP provides an upper bound for the dimensionality of the r-observable subspace.…”
Section: B the Meep With Respect To A Node And Node Observabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…where m * r = |π * r | is the size of the mEEP with respect to node r. Equation (37) states that the rank of the observability of a node under consensus dynamics is equal to the rank of the observability of its cell in the consensus dynamics of the corresponding quotient graph, and the size of the mEEP provides an upper bound for the dimensionality of the r-observable subspace.…”
Section: B the Meep With Respect To A Node And Node Observabilitymentioning
confidence: 99%
“…Finding a nontrivial EEP is thus equivalent to finding a graph (i.e., the quotient graph) for which its associated consensus dynamics describes the dynamics on the lower-dimensional synchronization manifold, which is invariant under the graph Laplacian [37,38].…”
Section: A Eep Consensus Is Preserved By the Full Laplacian Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, group or cluster synchronization problem for different kinds of multi-agent systems has recently been a rather significant topic in both theoretical research and practical applications. It is reported that, in general, two designed strategies have been effectively employed to realize group or cluster synchronization of networked multi-agent systems modelled by first-order or second-order integrator dynamics [12,14,20,21,22,25]. The first strategy is to aim at nonidentical agent dynamics in different groups with positive couplings [14,19,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, several kinds of network models have been proposed for the purpose of describing the real world more realistic [1,5,6,7,8]. In the complex dynamical networks, one of the most remarkable phenomena is their spontaneous synchronization, and so many types of synchronization, such as complete synchronization [9], phase synchronization [10], projective synchronization [11,12,13], impulsive synchronization [14,15,16], and cluster synchronization [17,18,19] have deeply caught the eyes of the researchers in the past few decades. However, the phenomenon of synchronization also can be classified into 'inner synchronization' [14,20] and 'outer synchronization' [21,22] from another point of view.…”
Section: Introductionmentioning
confidence: 99%